Secretion of Organic Acids by Phosphate Solubilizing Bacteria - Prijambada, Irfan Dwidya; Widada, Jaka; Kabirun, Siti; Widianto, Donny (JOURNAL OF TROPICAL SOILS, 2009)
Phosphorus availability is a major limiting for crop production.  Bacterial solubilization of insoluble inorganic phosphate has been studied as a means of providing available phosphorus for crop production.  Bacterial abilities to solubilize calcium phosphate and rock phosphate have been identified to be related with their abilities to produce gluconic acid and ketogluconic acid.  However, there is no information regarding the relationship between bacterial ability to solubilize aluminum phosphate and their ability to produce organic acids.  This study was conducted to investigate the relationship between bacterial ability to solubilize calcium and aluminum phosphates with their ability to produce organic acids.  Bacterial ability to solubilize calcium and aluminum phosphates were determined as the concentration of soluble phosphate in the filtrate of bacterial cultivation media, while bacterial ability to produce organic acids were assessed from the accumulated organic acids in its.  The results showed that bacterial abilities to solubilize calcium and aluminum phosphates well related to their abilities to produce organic acids.  Organic acids related with the solubilization of calcium phosphate differ from the ones relatedAlam, S., S. Khalil, N. Ayub,  and M. Rashid. 2002. In vitro solubilization of inorganic phosphate by phosphate solubilizing microorganisms (PSM) from maize rhizosphere. Int. J. Agri. Biol. 4: 454-458.Beauchemin, S., D. Hesterberg, J. Chou, M. Beauchemin, R.R. Simard, and D.E. Sayers. 2003. Speciation of phosphorus in phosphorus-enriched agricultural soils using X-ray absorption near-edge structure spectroscopy and chemical fractionation. J. Environ. Qual. 32:1809–1819.Bolan, N.S., R. Naidu, S. Mahimairaja, dan S. Baskaran. 1994. Influence of low-molecular-weight organic acids on the solubilization of phosphates. Biol. Fertil. Soils 18: 311-319.Cline, G.R., P.E. Powell, P.J. Szaniszlo, dan C.P. Reid. 1983. Comparison of the abilities of hydroxamic and other natural organic acids to chelate iron and other ions in soil. Soil Sci. 136: 145-157.Curtin, D., and J.K. Syers, 2001. Lime-induced changes in indices of soil phosphate availability. Soil Sci. Soc. Am. J. 65:147–152.Fox, T.R., N.B. Comerford, dan W.W. McFee. 1990. Phosphorus and aluminium release from a spodic Horizon mediated by organic acids. Soil Sci. Soc. Am. J. 54: 1763-1767.Hue, N.V., G.R. Craddock, dan F. Adams. 1986. Effect of organic acids on aluminium toxicity in subsoils. Soil Sci. Soc. Am. J. 50: 28-34.Johnson, S.E., and R.H. Loeppert. 2006. Role of organic acids in phosphate mobilization from iron oxide. Soil Sci. Soc. Am. J. 70:222–234.Kumari, A., K.K. Kapoor, B.S. Kundu, and R.K. Mehta. 2008. Identification of organic acids produced during rice straw decomposition and their role in rock phosphate solubilization. Plant Soil Environ. 54: 72–77Lopez-Hernandez, D., D. Flores, G. Siegert, dan J.V. Rodriguez. 1979. The effect of some organic anions on phosphate removal from acid and calcareous soils. Soil Sci. 128: 321-326.Lopez-Pineiro, A., dan A. Garcia-Navarro. 2001. Phosphate fractions and availability in Vertisols of South-Western Spain. Soil Sci. 166: 548-556.Olsen, S.R. dan Sommers, L.E. 1982. Phosphorus. In Page, A.L., Miller, R.H. & Keeney, D.R. (eds.). Methods of Soil Analysis. Part 2. 2nd ed. ASA and SSSA Publisher, Madison.Rao, W.V.B.S., and M.K. Sinha. 1963. Phosphate dissolving microorganisms in the soil and rhizosphere. Indian J. agric. Sci. 33: 272-278.Rodriguez, H., T. Gonzalez, I. Goire, dan Y. Bashan. 2004. Gluconic acid production and phosphate solubilization by the plant growth-promoting bacterium Azospirillum spp. Naturwissenschaften 91: 552-555.Sagoe, C.I., T. Ando, K. Kouno, and T. Nagaoka. 1997. Effect of organic-acid treatment of phosphate rocks on the phosphorus availability to Italian ryegrass. Soil Sci. Plant Nutr. 43: 1067-1072.Sanchez, P.A. 1976. Properties and Management of Soils in the Tropics. John Wiley & Sons, Inc. New York. 618 pp.Siddique, M.T., and J.S. Robinson. 2003. Phosphorus sorption and availability in soils amended with animal manures and sewage sludge. J. Environ. Qual. 32:1114–1121.Song, O.R., S.J. Lee, Y.S. Lee, S.C. Lee, K.K. Kim, dan Y.L. Choi. 2008. Solubilization of insoluble inorganic phosphate by Burkholderia cepacia DA23 isolated from cultivated soil. Braz. J. Microbiol. 39: 151-156.Sridevi, M., K.V. Mallaiah, and N.C.S. Yadav. 2007. Phosphate solubilization by Rhizobium isolates from Crotalaria species. J. Plant Sci. 2: 635-639.Traina, S.J., G. Sposito, D. Hesterberg, dan U. Kafkafi. 1986. Effects of pH and organic acids on orthophosphate solubility in an acidic, montmorillonitic soil. Soil Sci. Am. J. 50: 45-52.Trivedi, P., and T. Sa. 2008. Pseudomonas corrugata (NRRL B-30409) mutants increased phosphate solubilization, organic acid production, and plant growth at lower temperatures. Curr. Microbiol. 56: 140-144.Tunesi, S., V. Poggi, and C. Gessa. 1999. Phosphate adsorption and precipitation in calcareous soils: The role of calcium ions in solution and carbonate minerals. Nutr. Cycling Agroecosyst. 53:219–227.Zhang, M., A.K. Alva, Y.C. Li, dan D.V. Calvert. 2001. Aluminium and iron fractions affecting phosphorus solubility and reactions in selected sandy soils. Soil Sci. 166: 940-948.with the solubilization of aluminum phosphate.  Moreover, there is similarity in the production of organic acids related to the solubilization of aluminum phosphates and iron phosphate.